2011
DOI: 10.1177/0969733011398093
|View full text |Cite
|
Sign up to set email alerts
|

Placebo use in clinical practice by nurses in an Iranian teaching hospital

Abstract: The present study was carried out to explore Iranian nurses' use of placebos in clinical practice and their knowledge and attitude towards its use. A cross-sectional, descriptive study was conducted using self-report questionnaires. All nurses working in a university hospital in Arak (n=342) were invited to participate in the study. Among 295 respondents, 221 (75%) reported that they had used at least one placebo within the past year and 179 (81%) told patients they were receiving actual medication. The most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…Most of the others considered placebo use such as permitted if the experience in the department supports its efficiency (141, or 47.76%), or permitted if research supports its efficiency (91, or 30.84%). [20] In this study; 86.2% of hemodialysis nurses stated that their patients report pain relief and it had a therapeutic effect in 30 minutes after saline injection. In non-hemodialysis nurses, this ratio was found 68.6 percent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the others considered placebo use such as permitted if the experience in the department supports its efficiency (141, or 47.76%), or permitted if research supports its efficiency (91, or 30.84%). [20] In this study; 86.2% of hemodialysis nurses stated that their patients report pain relief and it had a therapeutic effect in 30 minutes after saline injection. In non-hemodialysis nurses, this ratio was found 68.6 percent.…”
mentioning
confidence: 99%
“…[12] Baghcheghi and Koohestani (2011) found that 23.07% of the nurses use placebo once a week on average and 63.08% use placebo once in a month on average. [20] In this study, 21.7% of hemodialysis nurses were using placebo mostly and 77.6% of them always preferred placebo for pain management for the first step of analgesia.…”
mentioning
confidence: 99%
“…Despite these ethical concerns, the use of placebo treatment in clinical practice is common both internationally and across disciplines [21][22][23][24][25]. For example, 75% of nurses in Iran [21], 88% of general practitioners in Germany [24], and 50% of internists and rheumatologists in the United States [25] admit to the deceptive use of placebo treatment in clinical practice.…”
Section: Attitudes Towards Health Care and The Providermentioning
confidence: 96%
“…For example, 75% of nurses in Iran [21], 88% of general practitioners in Germany [24], and 50% of internists and rheumatologists in the United States [25] admit to the deceptive use of placebo treatment in clinical practice. Reasons for the use of placebo treatment by health care providers appear well intentioned and include calming the patient, as supplemental treatment, to control pain, and as a bridge to the next regular dosage of medication [26].…”
Section: Attitudes Towards Health Care and The Providermentioning
confidence: 99%
“…In the nursing discipline, available studies have measured the perceived effectiveness of placebo as inert medication among rheumatology, haemodialysis and non‐haemodialysis nurses (Alaloul et al, ; Berthelot, Maugars, Abgrall, & Prost, ; Unver, Yildirim, & Unal, ); and also among the managerial (Nitzan & Lichtenberg, ) and clinical nurses (Baghcheghi & Koohestani, ) regarding their aptitudes in adopting placebo, mainly by using monocentric cross‐sectional surveys. Therefore, no large‐scale data have been published to date regarding the daily use of different CFs by nurses as well as their clinical decision process of implementation, such as in which conditions they are mostly effective and their ethical implications.…”
Section: Introductionmentioning
confidence: 99%